Drug interactions for elderly with respiratory disorders and times of COVID-19: a systematic scoping review - Forgerini, Marcela; Schiavo, Geovana; Lucchetta, Rosa Camila; Mastroianni, Patricia (Vitae, 2020)
Background: The elderly people have high morbimortality associated with respiratory disorders, in addition to the presence of other safety risk factors, such as the use of potentially inappropriate medication and the occurrence of drug interactions. Objective: Considering the current pandemic scenario, it was intended to identify explicit criteria-based tools that reported drug interactions between potentially inappropriate medication and respiratory system disorders and possibly worse prognosis of COVID-19 infection. Methods: A systematic scoping review was conducted until February 2020. Study characteristics of explicit criteria-based tools, and potentially inappropriate medication, drug interactions, and therapeutic management, were extracted. Results: Nineteen explicit criteria-based tools were included. Nineteen drug interactions and 17 potentially inappropriate medications with concerns for three respiratory disorders (asthma, chronic pulmonary obstructive disease, and respiratory failure) were identified. The most frequent pharmacological classes reported were benzodiazepines and beta-blockers. For clinical management, the tools recommend using cardioselective beta-blockers, calcium channel blockers, angiotensin-converting enzyme inhibitors, and angiotensin II type I receptor blockers, and benzodiazepines with a short or intermediate half-life. Conclusion: Considering the increased risk of COVID-19 infection in the elderly, drug interactions and the use of potentially inappropriate medication associated with the occurrence of adverse drug events in the respiratory system may also worsening COVID-19 infection in patients with uncontrolled respiratory disorders. Thus, it is essential to assess drug therapy in use, to identify safety risks, and monitor the elderly in general and those with a worse prognosis concerning COVID-19, promoting patient safety.